Ambiguous results of balloon angioplasty for central vein stenosis in hemodialysis patients with native arteriovenous fistula - Z. B. Kardanakhishvili; A. B. Zulkarnaev; B. V. Baykov; V. A. Stepanov (Вестник трансплантологии и искусственных органов, 2020)
Objective: to conduct comprehensive comparative analysis of the patency rate of native arteriovenous fistula (AVF) for central vein stenosis (CVS) after endovascular balloon angioplasty and palliative surgery. Materials and methods. The retrospective study included 80 patients with confirmed central vein stenosis: subclavian, brachiocephalic veins, inferior vena cava, or multiple lesions. The experimental group included 39 patients who underwent percutaneous balloon angioplasty. The control group included 41 patients who, for various reasons, did not do balloon angioplasty, but underwent palliative interventions: thrombectomy, proximalization of arteriovenous anastomosis, AVF blood flow-reducing surgical procedures. Results. Primary patency (time interval between the first intervention for CVS and the second intervention) in the experimental group was 61.5% [95% CI 44.5; 74.7] and 15.4% [95% CI 6.2; 28.3] at 6 and 12 months, respectively. In the control group, it was 39% [95% CI 24.3; 53.4] and 0% respectively. Hazard ratio (HR) 0.5337 [95% CI 0.3381; 0.8427], log-rank test p = 0.0011. No differences in functional primary patency (time interval between the start of using AVF and the first intervention for CVS) were found: 89.7% [95% CI 74.9; 96] and 30.8% [95% CI 17.3; 45.4] at 1 year and 3 years, respectively, in the experimental group, and 80.5% [95% CI 64.8; 89.7] and 24.4% [95% CI 12.7; 38.2] in the control group. There were no differences between the groups HR 0.7695 [95% CI 0.4952; 1.196], log-rank p = 0.2259. In the experimental group, strong negative correlation between primary patency and functional primary patency was detected: r = –0.627 [95% CI –0.787; –0.388], p < 0.0001. In the control group, no such correlation was found: r = 0.049 [95% CI –0.262; –0.351], p = 0.7599. Thus, the later CVS developed, the less effective balloon angioplasty was. Balloon angioplasty significantly increased duration of AVF use after first intervention for CVS (secondary patency): 84.6% [95% CI 68.9; 92.8], 66.7% [95% CI 49.6; 79.1] and 17.9% [95% CI 7.9; 31.3] at 6, 12 and 24 months, respectively in the experimental group. In the control group, it was 56.1% [95% CI 39.7; 69.6], 19.5% [95% CI 9.2; 32.7] and 0%. HR 0.4009 [95% CI 0.2481; 0.6477], log-rank p < 0.0001. Functional secondary patency (total duration of AVF use) was: 100%, 74.4% [95% CI 57.6; 85.3] and 12.8% [95% CI 4.7; 25.2] at 1, 3 and 5 years in the experimental group, and 95.1% [95% CI 81.9; 98.8], 36.6% [95% CI 22.3; 51] and 4.9% [95% CI 0.9; 14.5] in the control group. HR 0.5661 [95% CI 0.3598; 0.8906], log-rank p = 0.0067. Conclusions. 1. Central vein stenosis inevitably cuts vascular access from the ipsilateral side. 2. Balloon angioplasty allows to slightly prolong AVF use but it cannot radically change the long-term results of CVS treatment. 3. The outcome of balloon angioplasty greatly depends on the length of the period from the time the use of AVF started to the time CVS developed. 4. Multiple repeated balloon angioplasties are apparently justified in patients for whom creating a new vascular access might not be possible. 4. AVF volumetric blood flow velocity is an important factor determining the severity of CVS clinical manifestations and whether repeated surgical interventions are needed.